Staining and calculus formation after 0.12% chlorhexidine rinses in plaque-free and plaque covered surfaces: a randomized trial (Journal of Applied Oral Science, 2010)
OBJECTIVES: Studies concerning side effects of chlorhexidine as related to the presence of plaque are scarce. The purpose of this study was to compare the side effects of 0.12% chlorhexidine gluconate (CHX) on previously plaque-free (control group) and plaque-covered surfaces (test group). METHODS: This study had a single-blind, randomized, split-mouth, 21 days-experimental gingivitis design, including 20 individuals who abandoned all mechanical plaque control methods during 25 days. After 4 days of plaque accumulation, the individuals had 2 randomized quadrants cleaned, remaining 2 quadrants with plaque-covered dental surfaces. On the fourth day, the individuals started with 0.12% CHX rinsing lasting for 21 days. Stain index intensity and extent as well as calculus formation were evaluated during the experimental period. RESULTS: Intergroup comparisons showed statistically higher (p